Assessment of efficacy and safety by CalliSpheres versus HepaSpheres for drug-eluting bead transarterial chemoembolization in unresectable large hepatocellular carcinoma patients - Guangsheng Zhao; Song Liu; Songbai Chen; Zhizhong Ren; Chuang Li; Jie Bian; Jianlin Wu; Jun Zhou; Yuewei Zhang (Taylor & Francis Group, 2021)
This study aimed to compare efficacy and safety of HepaSpheres and CalliSpheres in unresectable large hepatocellular carcinoma (HCC) patients. One hundred and twenty-seven unresectable large HCC patients receiving drug-eluting bead transarterial chemoembolization (DEB-TACE) treatment with CalliSpheres or HepaSpheres microspheres were analyzed. Treatment response, Karnofsky performance status (KPS) score, adverse events, main liver function indexes, time to progression (TTP), and overall survival (OS) were analyzed. Objective response rate (82.7% vs. 63.8%, p=.030) and disease control rate (100.0% vs. 91.5%, p=.030) were increased in CalliSpheres group compared to HepaSpheres group at 1 month after treatment, while no difference was found between the two groups regarding treatment response at 3 or 6 months post treatment (all p>.05). The KPS score at 1, 3, and 6 months was similar between the two groups (all p>.05). As for the liver function, the ALT, AST, ALB, and TBIL levels at 7 and 30 days were of no difference between the two groups (all p>.05). In addition, the adverse events including nausea/vomiting, pain, fever, myelosuppression, biloma, and abscess were of no difference between the two groups, either (all p>.05). In terms of survival profile, there was no difference regarding TTP (6.3 months (95%CI: 5.9-6.6 months) vs. 6.0 months (95%CI: 5.6-6.4 months), p=.082) or OS (23.0 months (95%CI: 20.1-25.9 months) vs. 22.0 months (95%CI: 20.2-23.8 months), p=.571) between the two groups. In conclusion, CalliSpheres seems to be superior in short-term efficacy and equal in long-term efficacy as well as safety compared to HepaSpheres for DEB-TACE treatment in unresectable large HCC patients.